Synthesis of nanosized glass powders using non-transferred dc thermal plasma process. (1st July 2013) - Cho, S; Shim, H; So, K; Kim, S; Samal, S; Park, D; Kim, H
<x xml:space="preserve">Abstract</x> Abstract The fabrication of nanosized Bi2O3-ZnO-B2O3 based glass powder using a non-transferred direct current plasma process was examined. This paper discusses the amorphous and crystalline nature of glass systems that contain bismuth oxide after plasma treatment. The addition of a reactive gas (O2) enhanced the amorphous nature of the glass powder by preventing the thermal dissociation of Bi2O3 into nanosized bismuth particles. Transmission electron microscopy revealed the spherical shape of the powders with a size of 10-60 nm. A minor change of <1 mol.-% in the resulting powder composition was confirmed by inductively coupled plasma-optical emission spectrometry measurements. The nanosized glass powders began to shrink at 340°C, which is 50°C lower than the temperature at which micrometre sized glass powders begin shrinking. Fundamental information for the size reduction of the multicomponent glass system using dc thermal plasma technique as well as thermal behaviour was provided.